2021
DOI: 10.1186/s13023-021-01754-z
|View full text |Cite
|
Sign up to set email alerts
|

First French study relative to preconception genetic testing: 1500 general population participants’ opinion

Abstract: Background Until very recently, preconception genetic testing was only conducted in particular communities, ethnic groups or families for which an increased risk of genetic disease was identified. To detect in general population a risk for a couple to have a child affected by a rare, recessive or X-linked, genetic disease, carrier screening is proposed in several countries. We aimed to determine the current public opinion relative to this approach in France, using either a printed or web-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
0
10
0
1
Order By: Relevance
“…Table 1 gives an oversight of the main characteristics of the articles included. Authors were from the United States and Canada [ 25 32 ], Australia and New Zealand [ 13 , 33 , 34 ], the United Kingdom [ 35 , 36 ], the Netherlands, [ 2 , 5 , 20 , 37 49 ] Sweden, [ 14 , 50 53 ] Belgium [ 10 , 54 ], Israel, [ 6 , 55 57 ] France [ 58 ] and Cyprus [ 4 , 7 ], or consisted of a panel of European or international stakeholders [ 3 , 21 ]. Most articles were published after 2011.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 gives an oversight of the main characteristics of the articles included. Authors were from the United States and Canada [ 25 32 ], Australia and New Zealand [ 13 , 33 , 34 ], the United Kingdom [ 35 , 36 ], the Netherlands, [ 2 , 5 , 20 , 37 49 ] Sweden, [ 14 , 50 53 ] Belgium [ 10 , 54 ], Israel, [ 6 , 55 57 ] France [ 58 ] and Cyprus [ 4 , 7 ], or consisted of a panel of European or international stakeholders [ 3 , 21 ]. Most articles were published after 2011.…”
Section: Resultsmentioning
confidence: 99%
“…Most articles were published after 2011. [ 2 , 3 , 5 , 9 , 10 , 13 , 14 , 20 , 21 , 25 31 , 33 , 35 , 36 , 38 41 , 43 55 , 58 ] Multiple article types were present in this selection, including primary data of quantitative survey studies [ 30 , 38 , 44 , 48 , 50 , 58 ] and qualitative studies, [ 2 , 6 , 29 , 39 , 46 , 49 , 51 55 ] a witness seminar [ 41 ], a workshop with experts [ 3 ], descriptions of previous screening offers or evaluations thereof [ 21 , 40 , 42 , 43 , 57 ], theoretical papers [ 4 , 7 , 13 , 14 , 20 , 27 , 28 , 31 , 32 , 34 , 35 , 45 , 47 ], literature reviews [ 10 , 33 , 36 , 56 ], an expert consensus paper [ 5 ], cost-effectiveness analyses [ 25 , 26 ] and a sociotechnical analysis [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A strength in our study is the methodological approach of empirical bioethics. It allows us to combine qualitative analysis with an ethical discussion, maintaining a detailed analysis of descriptions of PECS by GPs, a group of clinicians who may play a crucial role in offering PECS8 12–14 and an analysis of ethical complexities. The in-depth nature of the interviews is also a strength of this study even though the relatively small sample in the interviews could be seen as a limitation.…”
Section: Discussionmentioning
confidence: 99%
“…Both in the Netherlands and internationally, GPs have been described as important in offering population-based PECS 12. Some studies have shown that the public prefers that GPs offer the test,13 14 rather than clinical geneticists or midwives,11 and it is probable that GPs will receive more questions about PECS as general knowledge of the practice increases 15. However, little is known about GPs’ views and experiences of PECS.…”
Section: Introductionmentioning
confidence: 99%